Compression Behavior of Basalt Fiber-Reinforced Polymer Tube-Confined Coconut Fiber-Reinforced Concrete - Yang Lv; Xueqian Wu; Yuhao Zhu; Xiao Liang; Quanxi Cheng; Mengran Gao (Advances in Materials Science and Engineering)
Basalt fiber is cheap and has excellent mechanical performance. In addition, in combination with the environmentally friendly coconut fiber, it can contribute to sustainable construction materials. In this study, a composite material consists of basalt fiber-reinforced polymer (BFRP) tube-encased coconut fiber-reinforced concrete (CFRC) is developed. The 28-day compression strength of the plain concrete is about 15 MPa, which represents the low strength and poor-quality concrete widely existing in a large number of old buildings. The concrete was poured and cured into the steel moulds, BFRP tubes with the inner diameter of 100 mm and a height of 200 mm, and BFRP tubes with the inner diameter of 160 mm and a height of 320 mm, respectively. In total, 36 cylindrical specimens were constructed and tested. The axial compression tests were carried out to examine the strength and ductility enhancement due to the confinement of the BFRP tubes and coconut fibers. Also, the existing models were used to predict the ultimate axial compression strength and strain. The results show that the size of the specimen significantly influences the predicted compression strength.